Simple and efficient enzymatic transglycosylation of stevioside by beta-cyclodextrin glucanotransferase from Bacillus firmus - Jaitak, V.; Kaul, V. Kumar; Bandna; Kumar, N.; Singh, B.; Savergave, L. S.; Jogdand, Vitthal V.; Nene, S. (Biotechnology Letters, 2009)
Stevioside was subjected to 1,4-intermolecular transglycosylation using beta-cyclodextrin glucanotransferase (beta-CGtase) produced from an alkalophilic strain of Bacillus firmus. The reaction was carried out by traditional, ultrasound-assisted and microwave-assisted techniques. Reaction under microwave conditions was faster and was completed in 1 min yielding two 1,4 transglycosylated products, 4'-O-alpha-d-glycosyl stevioside (I) and 4''-O-alpha-d-maltosyl stevioside (II) in 66% and 24%, respectively. The optimum transglycosylation occurred by using stevioside (1.24 mmol), beta-CD (1.76 mmol) and beta-CGtase (2 U/g) under microwave assisted reaction (MAR) in 5 ml sodium phosphate buffer (pH 7) at 50A degrees C and 80 W power. MAR is therefore potentially a useful and economical method for faster transglycosylation of stevioside.
Keywords: beta-cyclodextrin; beta-Cyclodextrin glucanotransferase; Microwave-assisted reaction; Stevia rebaudiana; Stevioside; Transglycosylation

Maltooligosaccharide forming amylases and their applications in food and pharma industry - Shinde, Vidhya K.; Vamkudoth, Koteswara Rao (Journal of Food Science and Technology-Mysore, 2022)
Oligosaccharides are low molecular weight carbohydrates with a wide range of health benefits due to their excellent bio-preservative and prebiotic properties. The popularity of functional oligosaccharides among modern consumers has resulted in impressive market demand. Organoleptic and prebiotic properties of starch-derived oligosaccharides are advantageous to food quality and health. The extensive health benefits of oligosaccharides offered their applications in the food, pharmaceuticals, and cosmetic industry. Maltooligosaccharides and isomaltooligosaccharides comprise 2-10 glucose units linked by alpha-1-4 and alpha-1-6 glycoside bonds, respectively. Conventional biocatalyst-based oligosaccharides processes are often multi-steps, consisting of starch gelatinization, hydrolysis and transglycosylation. With higher production costs and processing times, the current demand cannot meet on a large-scale production. As a result, innovative and efficient production technology for oligosaccharides synthesis holds paramount importance. Malto-oligosaccharide forming amylase (EC 3.2.1.133) is one of the key enzymes with a dual catalytic function used to produce oligosaccharides. Interestingly, Malto-oligosaccharide forming amylase catalyzes glycosidic bond for its transglycosylation to its inheritance hydrolysis and alternative biocatalyst to the multistep technology. Genetic engineering and reaction optimization enhances the production of oligosaccharides. The development of innovative and cost-effective technologies at competitive prices becomes a national priority.
Keywords: Glycosyl hydrolases; Isomaltooligosaccharides; Maltooligosaccharide; Maltooligosaccharide forming amylase; Transglycosylation